The organizational communication and the leadership: what is the relationship between the 360-degree evaluation and the leadership communication? - Mourão, Rita Monteiro (2018)
Organizational communication and evaluation processes play a key role for organizations, as they are responsible for better individual performance and consequently for greater organizational effectiveness (Proctor & Doukakis, 2003). In general, organizational communication may be defined as a way of disseminating information that enables coordination and conclusion of tasks, decision-making and conflict resolution (Ayub, Manaf & Hamzah, 2014). On the other hand, performance evaluation may be generically defined as a continuous process of monitoring and management that allows correcting of certain behaviors (Hosain, 2016). Over the years it has become clear that the traditional performance appraisal process (i.e., the top-down evaluation process in which the leader evaluates the subordinate) presents some limitations, such as non-confidentiality and quotation errors of the evaluators (Caetano, 2008). In this sense, it became necessary to promote other alternative forms of performance evaluation, such as the 360-degree performance evaluation.